SOME RELEVANT ETHICAL ISSUES IN RELATION TO FRESHWATER RESOURCES AND GROUNDWATER - Custodio, Emilio (Águas Subterrâneas, 2000)
Freshwater resources are limited and the demand is steadily growing. In some areas a large part of available water resources are already committed. Then, some degree of concern is a logical position. But it has to faces. One consists on making more freshwater available, which means more interference with the environment, altering the social context and depleting groundwater resources. The other consist on correcting the current, often highly inefficient use of freshwater, protecting groundwater reserves and preventing further degradation by contamination. These are ethical issues to be seriously considered before creating a stressed environment and wasting badly needed economical and human resources. Evaluation of available and developable freshwater resources has to be carried out together with the uncertainty of natural situations and processes, and looking for the long term sustainability in a changing framework. This sustainability is compatible with some kind of limited depletion of aquifer reserves. Groundwater is still a poorly managed and to some extent misunderstood, essential freshwater resource. Solving this handicap involves not only science and technology, but also clear economics, social appreciation and political will, all of them glued by ethical behaviour.